Convergence in Economic Growth and its Determinants : An Empirical Analysis / Mina Sabbaghpoor-Fard - Sabbaghpoor-Fard, Mina (2013)
For decades economic growth and its determinants have been the centre of attention among both theoretical and development economists. Theoretical economists have built models of economic growth while development economists are concerned as to how low-income countries can catch up with the rich ones, or, worse, become caught in a low-income trap. The persistence of poverty in some countries in the world and the failure to catch up has caused social scientists to not only review and debate the sources of economic growth but also to take the debate of convergence more seriously and try to provide different explanations. Neoclassical growth (NCGM) and new growth (NGM) theories, currently the main contending schools of thought, try to explain growth sources, and, by extension, convergence by focusing on capital accumulation and technological change, respectively. However, empirical studies using either model largely ignore the importance of institutions, on which there is increasing focus and discussion of economic performance, and globalization, which affects the economic welfare of countries. Therefore, in this research we try to reopen the debate of convergence incorporating these factors in re-estimating the above models. We do this by examining convergence for three groups of countries, which are classified by income according to the World Bank classification method, and by applying the GMM method to estimate the growth models. The results of this research show that the income level of countries is material when it comes to both the sources of growth and the speed of convergence. The debate over which model (NCGM or NGM) is appropriate is not that meaningful. Each model is appropriate for countries at particular levels of income, but not for the entire income range. The NCGM, which is believed to be obsolete by many economists, especially those who espouse the NGM, continues to be relevant for many countries of the world. Testing the convergence hypothesis in terms of GDP per capita shows that middle-income countries converge with high-income ones in both models. However, this only occurs very slowly in low-income countries. Therefore, we can conclude that income convergence is not monotonic and that an income threshold may need to be reached before convergence occurs. This shows the existence of a poverty trap. Investigating the role of institutions and globalization and innovation factors shows that these factors are the most important drivers of growth for middle-income and high-income countries but not for low-income countries. However, the effects of these variables were greatest across middle-income countries compared to high-income countries, which makes sense for the convergence hypothesis in both classes. Capital accumulation and secondary schooling are the most important drivers for low-income countries. This result again alerts us to the existence of an income threshold. Being more globalized and having stronger institutions does not work for these groups of countries unless they reach a certain level of income. This is consistent with the results of other researchers who find that ‘the tide of globalization does not lift all boats’.